Domestic Church: A New Frontier in Ecclesiology - Bourg, Florence Caffrey (Horizons, 2002)
This essay traces the revival of the concept of domestic church from Vatican II to the present. It identifies areas of preliminary consensus, as well as unresolved issues, which surface explicitly or implicitly in discussion of domestic church. Using Rahner's thought, the potential significance of domestic churches in ecclesiology is examined in more depth.